HERMENEUTIKA FENOMENOLOGIS HASAN HANAFI - Arifin, Muhammad Patri (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2018)
Al-Quran as a source of verbatim teachings requires a touch of understanding from humans to explore the meaning and contents. But in the process of touching meaning, often faced with a dilemma. On the one hand it is desirable to understand the meaning of the Qur'an in accordance with scientific and objective provisions, while the other side wants the presence of present reality for the creation of the moral interests and needs of Muslims today. So no wonder if various methodological offers emerge from contemporary Muslim thinkers, although the offer is different in the form of a framework, but is on the one goal that is to realize the nature of the Qur'an Shalihun Likulli Zaman wa Makan, the nature that desires the values universal in the contextualized Al-Quran, so that it can always be relevant in every age and place. Hasan Hanafi is one of the Muslim thinkers who assume that in digging the meaning of the Qur'an should see the needs and reality of Muslims in the Qur'an (subjective), not interpret the Quran as a whole regardless of the needs and guidance of Muslims. By this way, a mufassir is very important to have awareness of praxis as a form of realization of the meaning of the text in every day human life